2020
DOI: 10.1002/jimd.12279
|View full text |Cite
|
Sign up to set email alerts
|

Identification of neuronal structures and pathways corresponding to clinical functioning in galactosemia

Abstract: Classic galactosemia (OMIM# 230400) is an autosomal recessive disorder due to galactose-1-phosphate uridyltransferase deficiency. Newborn screening and prompt treatment with a galactose-free diet prevent the severe consequences of galactosemia, but clinical outcomes remain suboptimal. Five men and five women with classic galactosemia (mean age = 27.2 ± 5.47 years) received comprehensive neurological and neuropsychological evaluations, electroencephalogram (EEG) and magnetic resonance imaging (MRI). MRI data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“… 3 CAS is diagnosed in 24%–63% of children with CG, 5 , 58 , 66 , 69 compared with 0.1%–0.2% of children generally. 4 The fact that the cerebellum has been implicated in CG 70 , 71 may explain the confluence of fine and gross motor delays and CAS. Disordered language is seen in 50%–78% of children with CG, 65 , 66 , 68 compared with 7%–10% of children generally.…”
Section: Introductionmentioning
confidence: 99%
“… 3 CAS is diagnosed in 24%–63% of children with CG, 5 , 58 , 66 , 69 compared with 0.1%–0.2% of children generally. 4 The fact that the cerebellum has been implicated in CG 70 , 71 may explain the confluence of fine and gross motor delays and CAS. Disordered language is seen in 50%–78% of children with CG, 65 , 66 , 68 compared with 7%–10% of children generally.…”
Section: Introductionmentioning
confidence: 99%
“…Since neuropsychological assessment is sensitive for changes in cognitive functioning due to neurodegeneration in an early stage, 22 an ongoing pathophysiological process causing cognitive decline would likely have been detected by repeated neuropsychological assessment. Therefore, it is more likely that the cognitive impairment in CG originates in earlier developmental stages 23,24 . Importantly, the absence of cognitive decline in adults shows that the adults with normal to borderline intelligence in the current sample in their early and middle adulthood do not cognitively age faster than the general population.…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, it is more likely that the cognitive impairment in CG originates in earlier developmental stages. 23,24 Importantly, the absence of cognitive decline in adults shows that the adults with normal to borderline intelligence in the current sample in their early and middle adulthood do not cognitively age faster than the general population. Since this study does not include CG-patients with severe intellectual disabilities, no statements can be made about the cognitive aging of severely affected adult patients.…”
Section: Discussionmentioning
confidence: 75%
“…Subsequently, using diffusion tensor imaging, others found that compared to age-and gender-matched controls, patients with galactosemia had reduced volume in the left cerebellar white matter, the bilateral putamen, and left superior temporal sulcus. There was also lower fractional anisotropy and higher radial diffusivity values in the dorsal and ventral language networks compared to the controls [17] .…”
Section: Galactosemiamentioning
confidence: 75%